Effects of wearing masks during COVID-19 pandemic on the composition and diversity of skin bacteria and fungi in medical workers - Zhang, Jingxi; Jiang, Peiyun; Zhang, Yaxin; Liu, Wenlou; Kong, Shujing; Hou, Xiaoyang; Qi, Zuoyao; Sun, Yujin; Jiang, Guan (Frontiers in Microbiology, 2023)
Background Although studies have shown that wearing masks can affect the skin microbiome, more detailed and comprehensive research on wearing masks needs to be further explored.This study aimed to characterize the influence of mask wearing on the diversity and structural characteristics of the facial skin microbial community of medical staff during the COVID-19 pandemic by means of metagenomic sequencing (mNGS).Methods A total of 40 samples were taken by swabbing the cheek in the 2 × 2 cm 2 area before and after wearing the masks.DNA was extracted for metagenomic sequencing.Results A statistically significant decrease was found in the α diversity between BN and AN groups and between B2h and A2h groups. BN and AN mean groups before and after 8 hours of wearing the medical protective mask(N95),including 10 volunteers respectively.B2h and A2h mean groups before and after 8 hours of wearing masks,including 10 volunteers changing mask every 2 hours respectively.The β diversity was found to be statistically reduced between BS and AS groups(P=0.025), BN and AN groups(P=0.009), and B2h and A2h group(P=0.042). The fungal beta diversity was significantly decreased in every group before and after wearing masks.The main bacteria on the face before and after wearing masks were Cutibacterium (68.02% and 71.73%). Among the fungi, Malassezia predominated the facial skin surface before and after wearing masks (35.81% and 39.63%, respectively).Wearing different types of masks and changing masks according to different frequency will have different effects on the facial skin's microbiota.